Factors associated with influenza vaccination status of residents of a rural community in Japan - Watanabe Isao; Kuriyama Nagato; Ozasa Kotaro; Shigeta Masako; Matsui Daisuke; Watanabe Yoshiyuki (BMC, 2011)
Abstract Background The rate of influenza vaccination in Japan has declined over the past several decades. It is essential to identify community-specific factors that affect attitudes toward vaccination, but such parameters have not yet been fully determined in Japan. The present study used the Health Belief Model (HBM) to identify perceptions of influenza vaccination in a rural Japanese community. Methods All subjects were residents of a rural town in the southern part of Kyoto, Japan. An anonymous self-administered questionnaire was mailed to 846 randomly chosen households (containing 2,665 subjects). The survey explored gender, age, history of influenza, and factors associated with obtaining influenza vaccination, based on the HBM. Results A total of 1,182 valid responses (response rate, 44.4%) were received. Sources of information that were associated with vaccination decisions were medical facilities for children (OR = 4.21; 95% CI: 1.17-15.1), workplaces for adults (OR = 2.40; 95% CI: 1.22-4.75), medical facilities, town office and family for elderly subjects (OR = 6.18; 95% CI: 2.42-15.7, OR = 5.59; 95% CI: 2.26-13.8 and OR = 3.29; 95%CI: 1.01-10.6). Subjects, in all age groups, who strongly agreed that the vaccine was effective were significantly more likely to be vaccinated (OR = 10.5; 95%CI: 2.68-41.7 for children; OR = 8.85; 95%CI: 4.61-16.9 for adults; OR = 19.9; 95%CI: 8.28-48.0 for the elderly). The vaccination rate of elderly subjects who expressed concerns regarding adverse vaccine effects (OR = 0.34, 95% CI: 0.15-0.78) or who were worried about practical barriers to the vaccination process (OR = 0.13; 95% CI: 0.05-0.31) was significantly lower than in other populations. Conclusions Our results indicate that vaccination coverage can be increased if accurate information on personal risk, severity of influenza illness, and efficacy of vaccination are provided by responsible information sources that are easily accessible. Such sources include medical facilities and municipal offices. In addition, barriers and inconveniences associated with vaccination should be removed, especially if they impact on elderly people.